The evolution of physical attributes of the basketball players from the student team of the Chinese university, through the lens of functional training - Tszyun, Y.; Makeeva, V. S.; Chernov, S. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to empirically validate the enhancement of the physical abilities of the male basketball players from the Chinese university team through the implementation of functional training.